Structural Plasticity Limit, Shakedown and Dynamic Plastic Analyses of Structures - Yu, Maohong; Li, Jianchun; Ma, Guowei; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2009)
Limit and shakedown analysis for structures can provide a very useful tool for design and analysis of engineering structures. "Structural Plasticity - Limit, Shakedown and Dynamic Plastic Analyses of Structure" provides more general solutions of limit and shakedown analysis for structures by using a unified strength theory. A series of solutions of plates from circular, annular plates to rhombus plates and square plates, rotating discs and cylinders, pressure vessels are presented. These results encompass the Tresca-Mohr-Coulomb solution of structure as special cases. The unified solution, which cannot be obtained by using a single criterion, is suitable to more materials and structures. Maohong Yu is professor of Department of Civil Engineering at Xi'an Jiaotong University, China. He has authored 12 books including "Unified Strength Theory and Its Applications" and "Generalized Plasticity".
Fundamental Concepts of Stress and Strain -- Yield Condition -- Theorems of Limit Analysis -- Plastic Limit Analysis for Simply Supported Circular Plates -- Plastic Limit Analysis of Clamped Circular Plates -- Plastic Limit Analysis of Annular Plate -- Plastic Limit Analyses of Oblique, Rhombic, and Rectangular Plates -- Plastic Limit Analysis of Pressure Vessels -- Dynamic Plastic Response of Circular Plate -- Limit Angular Speed of Rotating Disc and Cylinder -- Projectile Penetration into Semi-infinite Target -- Plastic Analysis of Orthogonal Circular Plate -- Unified Limit Analysis of a Wellbore -- Unified Solution of Shakedown Limit for Thick-walled Cylinder -- Unified Solution of Shakedown Limit for Circular Plate -- Shakedown Analysis of Rotating Cylinder and Disc.
Keywords: Engineering; Structural mechanics; Mechanical engineering; Civil engineering; Buildings -- Design and construction; Building; Construction; Engineering, Architectural; Engineering; Building Construction; Structural Mechanics; Civil Engineering; Mechanical Engineering; Electronic books